Administration Building California Polytechnic College (1945)
View of the clock tower on the 'new' administration building, also known as the Second Administration Building (clocktower building) (built in 1941- 42) [now the Business Administration Building] from northwest angle, from behind eucalyptus trees. Corner of the old Household Arts (Agricultural Education) Building is visible. Published in May 1945 Bulletin (Series 26, no. 1)